The challenges of SENNOVA in the training projects of integral professional training - Restrepo García, Carlos Andrés
In this article is presented the role and articulation of the System of Research, Technological Development and Innovation (SENNOVA) in the training project of the comprehensive professional training of the SENA. The authors start from a need presented by training centers in the development of training projects, from applied research and mainstreaming to the SENA's technological lines. For this, some challenges associated with the implementation of SENNOVA research methodologies in the development of integral professional training are formulated.